Farmer preference for seed quality: a discrete choice experiment with tomato growers in Nepal. (2016) - Timsina, Krishna P.; Jourdain, Damien; Shivakoti, Ganesh P.
We developed discrete choice experiments (DCEs) to analyse farmers' preferences and willingness to pay (WTP) for tomato seed quality attributes in Nepal. Technology choices in a utilitarian framework were incorporated to examine the demand for seed quality attributes. Normal multinomial logit model (MNL) and random parameters logit model (RPL) were used to analyse the preferences and willingness to pay for seed quality attributes such as germination, vigour, purity and price. The preference heterogeneity in germination and vigour were analysed using RPL model where we added interactions of these attributes with socioeconomic variables. From both models, it was found that the farmers were more likely to pay for vigour followed by germination and purity. Looking at the WTP for tomato seed quality attributes and the price increment in new seeds through introduction of new post-harvest techniques, there is scope for suppliers to provide seeds having high percentage of vigour, germination and purity, respectively to make existing value chain more efficient.